Green Marketing dalam Membentuk Keputusan Pembelian - Ariestania, Adinda Rizki; Adriyanto, Andhy Tri (JURNAL ILMIAH MANAJEMEN & BISNIS, 2024)
Purpose – To analyze the influence of Green Products, Green Promotion, and Green Price on    Consumer Behavior and Purchasing DecisionsMethodology  –The method used is quantitative with multiple linear regression analysis, data collection through questionnaires, and purposive sampling techniques to determine the sample. All data that was collected was analyzed and processed using SPSS version 21.Findings – The results of this research show that there is a positive influence between Green Marketing, which consists of Green Products, Green Prices, and Green Promotion, on Consumer Behavior and Purchasing Decisions, but partially the value of the influence of Consumer Behavior on Purchasing Decisions is still in the relatively good category.Originality/Novelty –This research combines green marketing variables such as green products, promotion, and prices regarding consumer behaviour and purchasing decisions.Implications  –For the author, this research broadens insight into the application of green marketing in influencing consumer behaviour and purchasing decisions and strengthens understanding regarding sustainability. For academics, this research increases knowledge about the factors affecting buying decisions and consumer behaviour from a green marketing perspective and provides a basis for further research on sustainability strategies. This research provides insights for designing effective green marketing strategies for companies, strengthening environmentally friendly brand images, increasing competitiveness, and supporting business sustainability.